The use of Ginkgo biloba in healthy elderly - Franke, Andreas G. (Springer Netherlands, 2013)
To promote health-conscious behavior in the aging society and gain insight into the sources of knowledge on which preventive strategies are based, analyzing the behavior of elderly people who are recognized as highly health conscious may be useful. We focused on the use of Ginkgo biloba, which is commonly considered to be effective in preventing cognitive decline and dementia, among elderly adults. A total of 1,672 questionnaires were distributed among geriatric participants (60–94 years) who attended university lectures at 22 universities throughout Germany. Response rate was 36.1 %. We collected data on demographic characteristics, preventive strategies (use of Ginkgo and other supplements), health-conscious behavior, sources of knowledge concerning health behavior, and factors associated with the participants’ concept of aging. The prevalence of Ginkgo use was 15.3 %. Ginkgo was assumed to be effective for cognitive enhancement and the treatment of cognitive decline by two thirds of the surveyed participants and one third believed Ginkgo to be effective for preventing dementia. Ginkgo use was significantly higher among participants using natural remedies and herbal and food supplements. The use of Ginkgo was recommended by physicians (57.3 %), chemists (16 %), and healthcare magazines (10.7 %). Food supplements were taken by 65.8 % of the sample: this percentage was significantly higher among subjects who exhibited health-conscious behavior. “Knowledge” about strategies to enhance cognition or prevent cognitive decline among the elderly do not appear to be evidence based. Thus, there is a need to establish reliable and independent sources of scientific information for healthcare professionals and the general public.